Parental experiences of their infant's hospitalization for cardiac surgery. (4th February 2015) - Kosta, L.; Harms, L.; Franich‐Ray, C.; Anderson, V.; Northam, E.; Cochrane, A.; Menahem, S.; Jordan, B.
Abstract: Background: Parents are increasingly recognized as important partners in children's health care. Despite their involvement in care, parental experiences of their child's hospitalization have received little research attention. In this study we explored parents' perceptions of what they found difficult, what they would like to be different and what they found to be helpful during their infant's hospitalization and surgery for the treatment of congenital heart disease. Methods: Structured interviews were conducted with 154 parents (91 mothers, 63 fathers) whose infant underwent cardiac surgery (at <3 months of age) 1 month post discharge from hospital. Thematic and frequency analyses were performed. Results: Parents reported a range of difficulties from dealing with their baby's unfolding illness, surgery and recovery to the structural and systemic issues associated with the broader context of their experiences. In an effort to be near their baby, parents struggled to obtain the necessities for daily living at the hospital and negotiate transitions between their hospital and home lives throughout the admission. Domains parents identified for change included the availability of facilities and resources and the quantity and quality of information and emotional support. Parents reported relationships with hospital staff as the most common source of support during this challenging time. Conclusions: Opportunities to improve parents' experiences when their infant is in hospital exist at an organizational level as well as at the clinical level. The significance of parents' relationship with hospital staff indicates the potential for each professional to impact on families' experiences on a daily basis. The range of challenges indicates the scope and need for allied health services.